Social Communication in Maintaining Religious Tolerance Juntikebon Village Government, Juntinyuat Subdistrict - Maulidah, Nur Hasyim (Universitas Syiah Kuala, 2024)
This research aims to investigate the social communication conducted by the Juntikebon Village Government in Juntinyuat Sub-District in Maintaining Religious Tolerance. The research utilizes a descriptive qualitative research method, employing data collection techniques such as observation and interviews. The data excavation in this research utilizes interview techniques, with the interviewed parties including, Secretary of Juntikebon Village and Head of Juntikebon Village. The theories employed in data excavation are social communication theory and tolerance theory. Based on the research findings, the social communication conducted by the Juntikebon Village government in implementing the value of religious tolerance shows that there is social communication established between the community and the government. It can be concluded that the social communication of the Juntikebon Village government in Maintaining Harmony of Religious Tolerance in Juntikebon Village, Juntinyuat Sub-District, becomes one of the significant values for community life, contributing to building the village regardless of social strata or religion, as religion is the right and obligation of every individual. Hence, there is no business for the government, as stated in the 1945 Constitution and Pancasila. Thus, the village community and the government do not discriminate between Islam and Christianity.